Pediatric laryngeal carcinoma in a heterozygous carrier of Fanconi anemia. Issue 8 (31st January 2017) - D'Souza, A. M.; Mark, J.; Demarcantonio, M.; Leino, D.; Sisson, R.; Geller, J. I.
Abstract: A case of invasive, keratinizing squamous cell carcinoma of the larynx in an 8‐year‐old female treated with laryngectomy is presented. Perinatal exposure to human papilloma virus and constitutional heterozygosity for a FANCC mutation were identified, though FANCC heterozygosity is not known to be cancer predisposing. An additional tumor‐associated mutation in NOTCH1 was also identified potentially contributing to oncogenesis. This case illustrates an exceedingly rare type of cancer in the pediatric population and discusses diagnostic workup, evaluation of risk factors for head and neck cancer, and treatment options.